Classification of Population Data of Nagari Based on Economic Level Using The K-Nearest Neighbor Method - Mardiah, Ainil; Defni, Defni; Lestari, Aster Happy; Junaldi, Junaldi; Ritmi, Titin (International Journal of Advanced Science Computing and Engineering, 2024)
The process of collecting data and classifying the level of economic status of the residents of Nagari is currently manual, so the efficiency in data collection is less than ideal. As a result, the population of Nagari is not well controlled by government authorities due to the lack of detailed government supervision. Therefore, a classification application system is needed that can overcome these problems. In making a classification application system, it will be analyzed using the K-Nearest Neighbor method for grouping the economic level of the community, where data from each occupant of Nagari is used as criteria. It is hoped that this classification application can facilitate the grouping of the economic class of the population, so that the regent of village can make decisions on assistance from the system.